Velocity distribution of women`s 30-km cross-country skiing during Olympic Games from 2002-2014 - Erdmann, W. S.; Dancewicz-Nosko, D.; Giovanis, V. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Within several investigated endurance sport disciplines the distribution of load of the best competitors has a manner of evenly or slightly rising velocity values. Unfortunately many other competitors have usually diminishing values or when they are very poor they have evenly values. The aim of this study was to investigate distribution of velocity within 30-km cross-country female skiers. METHODS: Cross-country skiing runs were investigated of Olympic Games 2002-2014 (Salt Lake City, Turin, Vancouver, Sochi). At every race two 15 km or three 10 km loops of the same vertical profile were taken into account. The competitors were divided onto: A) winners; B) medalists; C) competitors who obtained places 4 to 10 at the finish line (medium runners); and D) competitors who obtained places 11 to 30 at the finish line (poor runners). Velocity data presented on the web pages of several institutions were utilized. RESULTS: The competitors had their velocity distributed in a manner with usually diminishing values. While comparing velocity of sequential loops with the mean velocity the difference for the poor runners reached the value of almost 6%, which was too high. There was significant (usually negative) correlation coefficient between values of velocity deviation for the first and second loops and the mean value of velocity for the entire distance for the better runners and mixed, i.e. positive and negative values for the poorer runners. CONCLUSIONS: It was postulated investigations of velocity distribution should be introduced in coaching in order to inform competitors about their running. This advises is especially important for the poorer runners. Up to now cross-country skiers run for themselves. It should be discussed whether the tactics used by road and track runners, i.e. running with pace makers, can be introduced in cross country skiing. Also the use of a drone during training can be used in order to maintain proper pace.